PENGARUH MOTIVASI DAN EMOTIONAL INTELLIGENCE TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada SMPN Se-Kecamatan Sragi Pekalongan) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to examine the effect of Motivation and Emotional Intelligence on Performance Master of Organizational Commitment as mediation (Studies in SMP Sragi District of Pekalongan. Total population in this study was 112 respondents , the sampling method used in this study sensus. Testing in this study is , using test instruments to test the validity and reliability testing. Testing for normality, using the classical assumption test, multicollinearity and heteroscedasticity. Testing the model using the coefficient of determination test and F-test , Hypothesis Testing using the t (test). Testing mediation effects by using path analysis path. Based on the findings of the study are as follows : motivation positively influences organizational commitment, emotional intelligence has a positive effect on organizational commitment, motivation has a positive effect on teacher performance, emotional intelligence and have a positive effect on teacher performance, organizational commitment has a positive effect on performance teacher , organizational commitment did not mediate the effect of motivation on the performance of teachers but of organizational commitment mediates the effect of emotional intelligence on the performance of teachers. Keywords : Motivation, Emmotional Intelligence, Organizational Commitment, Teacher Performance .